Downshiftology healthy meal prep : 100+ make-ahead recipes and quick-assembly meals - Bryan, Lisa (Clarkson Potter/Publishers, 2022)
"When Lisa Bryan began meal prepping several years ago, she quickly became bored eating leftovers and was wasting food. At the same time, she realized she needed to 'downshift' the accelerated pace of her life. Seeking balance, she made dietary changes, eating more vegetables and simple proteins, while eliminating gluten (she has celiac disease), processed foods, and reducing refined sugar. Then she flipped the script on meal prep by focusing on individual ingredients. On a whim, she posted a video to YouTube which went viral and she realized how many people were out there, just like her, who wanted a fresh approach to meal planning. By prepping a handful of ingredients at the start of the week--such as flaked salmon, zucchini noodles, peas, prosciutto, soft-boiled eggs, and roasted veggies--and then mixing and matching them throughout the week, she found that she could enjoy a variety of meals and snacks (Creamy Salmon Zoodles, Peas and Prosciutto with Jammy Eggs, and Strawberries, Avocado, and Arugula Salad) without getting fatigued. Lisa's debut cookbook is packed with 100 simple and ingenious, big-batch recipes that can either be frozen or repurposed into delicious meals without resembling leftovers. A dinner of light coconut chickpea curry with rice can be enjoyed the next day atop a tortilla for a crispy tostada at lunch, or as a chickpea shakshuka for breakfast. All of the recipes are gluten-free, low in refined sugar; many are naturally anti-inflammatory, and dairy is minimal and optional. Lisa's approachable method for eating well and preparing meals with ease will inspire home cooks to downshift, too--at least when it comes to making healthy meals without a fuss"--